2021
DOI: 10.1021/acs.joc.1c00618
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Gas-Phase Reactivity of Charged Pyridynes

Abstract: The reactivities of three isomeric, charged ortho-pyridynes, the 1,2-, 2,3-, and 3,4-didehydropyridinium cations, were examined in the gas phase using Fourier-transform ion cyclotron resonance (FT-ICR) mass spectrometry. The structures of selected product ions were probed using collision-activated dissociation (CAD) experiments in a linear quadrupole ion trap (LQIT) mass spectrometer. Mechanisms based on quantum chemical calculations are proposed for the formation of all major products. The products of the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…This reaction has been previously reported for organic compounds not undergoing radical reactions, such as ortho-benzynes, and it involves nucleophilic addition of the carbon−carbon double bond of allyl iodide to the cation followed by a homolytic C−I bond cleavage. 25,27,28 Upon reactions with cyclohexane, no single hydrogen atom abstraction products were detected for 1−4 (Table 1), in contrast to what has been reported for many carbon-centered radicals. 24,27,28 Instead, abundant product ions were formed that formally correspond to the addition of two hydrogen atoms to the oxenium cations.…”
Section: ■ Methodsmentioning
confidence: 64%
See 4 more Smart Citations
“…This reaction has been previously reported for organic compounds not undergoing radical reactions, such as ortho-benzynes, and it involves nucleophilic addition of the carbon−carbon double bond of allyl iodide to the cation followed by a homolytic C−I bond cleavage. 25,27,28 Upon reactions with cyclohexane, no single hydrogen atom abstraction products were detected for 1−4 (Table 1), in contrast to what has been reported for many carbon-centered radicals. 24,27,28 Instead, abundant product ions were formed that formally correspond to the addition of two hydrogen atoms to the oxenium cations.…”
Section: ■ Methodsmentioning
confidence: 64%
“…However, these product ions are likely formed upon an initial hydride anion abstraction followed by a proton abstraction (see discussion below), as previously reported for some aromatic even-electron cations. 24,27,28 Based on the above observations, it can be concluded that 1−4 do not contain unpaired electrons.…”
Section: ■ Methodsmentioning
confidence: 85%
See 3 more Smart Citations